Curating the gnomAD database: Report of novel variants in the thyroid peroxidase gene using in silico bioinformatics algorithms and a literature review. (1st December 2022) - Molina, Maricel F.; Pio, Mauricio Gomes; Scheps, Karen G.; Adrover, Ezequiela; Abelleyro, Miguel M.; Targovnik, Héctor M.; Rivolta, Carina M.
Abstract: Thyroid peroxidase (TPO) is a membrane-bound glycoprotein located at the apical side of the thyroid follicular cells that catalyzes both iodination and coupling of iodotyrosine residues within the thyroglobulin molecule, leading to the synthesis of thyroid hormone. Variants in TPO cause congenital hypothyroidism (CH) by iodide organification defect and are commonly inherited in an autosomal recessive fashion. In the present work, we report a detailed population analysis and bioinformatic prediction of the TPO variants indexed in the Genome Aggregation Database (gnomAD) v2.1.1. The proportion of missense cysteine variants and nonsense, frameshift, and splice acceptor/donor variants were analyzed in each ethnic group (European (Non-Finnish), European (Finnish), African/African Americans, Latino/Admixed American, East Asian, South Asian, Ashkenazi Jewish, Other). The results showed a clear predominance of frameshift variants in the East Asian (82%) and European (Finnish) (75%) population, whereas the splice site variants predominate in African/African Americans (99.46%), Other (96%), Latino/Admixed American (94%), South Asian (86%), European (Non-Finnish) (56%) and Ashkenazi Jewish (56%) populations. The analysis of the distribution of the variants indexed in gnomAD v2.1.1 database revealed that most missense variants identified in the An peroxidase domain map in exon 8, followed by exons 11, 7 and 9, and finally in descending order by exons 10, 6, 12 and 5. In total, 183 novel TPO variants were described (13 missense cysteine's variants, 158 missense variants involving the An peroxidase domain and 12 splicing acceptor or donor sites variants) which were not reported in the literature and that would have deleterious effects on prediction programs. In the gnomAD v2.1.1 population, the estimated prevalence of heterozygous carriers of the potentially damaging variants was 1:77. In conclusion, we provide an updated and curated reference source of new TPO variants for application in clinical diagnosis and genetic counseling. Also, this work contributes to elucidating the molecular basis of CH associated with TPO defects. Highlights: We report an analysis of the thyroid peroxidase variants indexed in the gnomAD database. A detailed population and bioinformatic analysis was performed. Missense and splice site variants were evaluated using sequence predictors. In total, 183 novel thyroid peroxidase variants were described. This work contributes to the knowledge of congenital hypothyroidism.